THE COMPERATIVE ANALYSIS OF CONSUMER BUYING DECISION OF ALL NEW JAZZ AND ALL NEW YARIS CARS (Case Study : Manado) - Monangin, Phamella Patrycia (Universitas Sam Ratulangi, 2015)
The needs of people are usually accompanied by a desire to have the latest vehicles that follow the trend is an opportunity that must be met. jazz and Yaris cars into favorite consumers in Manado. The purpose of this study was to find out whether there is significance influence between Culture, Social, Personal, and Psychological on Customer Buying Decision of All New Jazz and All New Yaris in Manado. The method of this research is purposive analysis and the data is obtained from questionnaire that distribute to the consumer All New Jazz and All New Yaris. The analysis method Independent Sample T-Test All New Jazz and All New Yaris in Manado. Based on the research that has been conducted, the result showed that Culture, Social, Personal, and Psychological. There’s no significant differences in Customer Buying Decision based on Culture Factor and Social Factor between All New Jazz and All New Yaris in Manado. However, there’s significant differences in Customer Buying Decision based on Social and Psychological Factor between All New Jazz and All New Yaris in Manado. Keywords: buying decision, consumer, culture, social, personal, psychological